Investigations into Hypoxia and Oxidative Stress at the Optic Nerve Head in a Rat Model of Glaucoma - Chidlow, Glyn; Wood, John P. M.; Casson, Robert J. (Frontiers in Neuroscience, 2017)
The vascular hypothesis of glaucoma proposes that retinal ganglion cell axons traversing the optic nerve head (ONH) undergo oxygen and nutrient insufficiency as a result of compromised local blood flow, ultimately leading to their degeneration. To date, evidence for the hypothesis is largely circumstantial. Herein, we made use of an induced rat model of glaucoma that features reproducible and widespread axonal transport disruption at the ONH following chronic elevation of intraocular pressure. If vascular insufficiency plays a role in the observed axonal transport failure, there should exist a physical signature at this time point. Using a range of immunohistochemical and molecular tools, we looked for cellular events indicative of vascular insufficiency, including the presence of hypoxia, upregulation of hypoxia-inducible or antioxidant-response genes, alterations to antioxidant enzymes, increased formation of superoxide, and the presence of oxidative stress. Our data show that ocular hypertension caused selective hypoxia within the laminar ONH in 11/13 eyes graded as either medium or high for axonal transport disruption. Hypoxia was always present in areas featuring injured axons, and, the greater the abundance of axonal transport disruption, the greater the likelihood of a larger hypoxic region. Nevertheless, hypoxic regions were typically focal and were not necessarily evident in sections taken deeper within the same ONH, while disrupted axonal transport was frequently encountered without any discernible hypoxia. Ocular hypertension caused upregulation of heme oxygenase-1 – an hypoxia-inducible and redox-sensitive enzyme – in ONH astrocytes. The distribution and abundance of heme oxygenase-1 closely matched that of axonal transport disruption, and encompassed hypoxic regions and their immediate penumbra. Ocular hypertension also caused upregulations in the iron-regulating protein ceruloplasmin, the anaerobic glycolytic enzyme lactate dehydrogenase, and the transcription factors cFos and p-cJun. Moreover, ocular hypertension increased the generation of superoxide radicals in the retina and ONH, as well as upregulating the active subunit of the superoxide-generating enzyme NADPH oxidase, and invoking modest alterations to antioxidant-response enzymes. The results of this study provide further indirect support for the hypothesis that reduced blood flow to the ONH contributes to axonal injury in glaucoma.